Preparation of homoallylic amines via a three-component coupling process. Issue 36 (5th September 2018) - Ou, Xiaoxu; Labes, Ricardo; Battilocchio, Claudio; Ley, Steven V.
Abstract : A three-component synthesis of homoallylic amines is described. Abstract : A three-component synthesis of homoallylic amines is described. The allylboronic species were generated in situ by homologation of vinyl boroxines with trimethylsilyldiazomethane, then followed by trapping of the allylboron intermediate with imines. Twenty-seven compounds were successfully prepared in moderate to high yields. Imines bearing various functional groups were tolerated, including aliphatic, aromatic and heteroaromatic substituents. Further elaboration of some of the homoallylic amines to form azeditines is also reported.